FRAND in the system of overcoming unfair competition - POLIKARPOV Антон (Ius Modernum, 2025)
The risks and abuses related to licensing standard-essential patents (SEPs) on fair, reasonable, and non-discriminatory (FRAND) terms have been studied. The main focus is on analyzing practices such as patent hold-up (abuse of the exclusive right of the SEP holder), patent ambush (concealed patenting with an attempt of gaining benefits after standardization), royalty stacking, and hold-out (the refusal of a licensee to conclude an agreement). The judicial and regulatory practices of the EU and the USA have been analyzed, showing that non-compliance with FRAND commitments leads to market monopolization, hinders the implementation of innovations, and creates barriers to fair competition. It has been proven that effective application of the FRAND mechanism is a key tool in countering the abuses of SEP holders. A special emphasis is placed on the Ukrainian context: it is noted that there is a lack of specific regulation of SEP/FRAND, which creates potential risks for the development of the telecommunications and technology sectors. The directions for improving legislation taking into account foreign experience have been proposed. The research hypothesis is that proper implementation of FRAND commitments is a necessary condition for reducing anticompetitive risks. The research methodology is based on formal-legal, comparative-legal, and analytical methods, using case law, regulatorʼs policies, and doctrinal sources.